2011
DOI: 10.4104/pcrj.2011.00096
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of asthma management by general practitioners in Karachi, Pakistan: comparison with international guidelines

Abstract: Background: Suboptimal management of asthma by general practitioners (GPs) can lead to poor health outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“… 34 In addition, the number of PCPs who had adequate knowledge practice in asthma management in a study in Pakistan is very low as 10.4%. 36 With asthma treatment in general (both starting and adjustment), the percentage of physicians who achieved ≥50% of correct answers (≥5/9) for all nine questions on treatment in our study is 22% ( Figure 1B ); this is roughly similar to that in the same format study in Hong Kong (32%). 28…”
Section: Discussionsupporting
confidence: 79%
“… 34 In addition, the number of PCPs who had adequate knowledge practice in asthma management in a study in Pakistan is very low as 10.4%. 36 With asthma treatment in general (both starting and adjustment), the percentage of physicians who achieved ≥50% of correct answers (≥5/9) for all nine questions on treatment in our study is 22% ( Figure 1B ); this is roughly similar to that in the same format study in Hong Kong (32%). 28…”
Section: Discussionsupporting
confidence: 79%
“…Another reason could be failure by clinicians to prescribe MDIs due to concerns about their intermittent availability and prohibitive cost to patients [ 31 ]. Conversely, clinicians in the developing world may lack the knowledge on what medications to use for asthma treatment, commonly prescribing oral SABA and oral steroid for long-term management [ 32 , 33 ]. Ultimately, even when physicians do prescribe inhaled medications, some patients may just prefer the oral route due to various negative preconceived ideas about MDIs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is known to reduce the efficacy of ICS [19]. Taken together, we speculate that these differences were related to inappropriate education and insufficient clinical skills by GP [8,10,11,20].…”
Section: Discussionmentioning
confidence: 85%
“…Unfortunately, not all GPs adhere to these guidelines [8]. In fact, evidence suggests under-treatment of asthmatics by Japanese physicians [9], and some studies have reported that GPs lag behind RS with regard to the management of asthma [8,10,11].…”
Section: Introductionmentioning
confidence: 99%